Covid-19 in Egyptian hemodialysis and kidney transplant children: retrospective analysis of single center experience - Fatina I. Fadel; Samar Sabry; Mohamed A. Abdel Mawla; Rasha Essam Eldin Galal; Doaa M. Salah; Rasha Helmy; Yasmen Ramadan; Wessam Elzayat; May Abdelfattah; Eman Abobakr Abd Alazem (BMC, 2022)
Abstract Background Chronic kidney disease stage 5 (CKD 5) populations have peculiar risk for severe Covid-19 infection. Moreover; pediatric data are sparse and lacking. The aim of this study is to report our experience in CKD 5 children treated by hemodialysis (CKD 5D) and CKD 5 children after kidney transplantation (KTR) during one year of Covid-19 pandemic. Methods Retrospective analysis of 57 CKD 5 children with Covid-19 like symptoms during 1 year pandemic was performed. A cohort of 19 confirmed patients (13 CKD 5D and 6 KTR) was analyzed in details as regard clinical, laboratory, radiological criteria, management and their short term outcome. Results Conclusion Pediatric patients on regular HD (CKD 5D) are at higher risk and worse outcome of Covid-19 infection than KT recipients (KTR). Pre-existing HTN and shorter duration after KT are potential risk factors. Reversible AGD after KT and CVC related infections in HD patients are additional presenting features of Covid-19 infection.